Description of three dimensional solvable evaluation algebras - Mukhamedov, Farrukh; Omirov, Bakhrom; Qaralleh, Izzat (Springer Science+Business Media Singapore 2014, 2014)
The concept of evolution algebras lies between algebras and dynamical system. In this paper we are going to describe three dimensional nilpotent, solvable evolution algebras. It is seen that three dimensional nilpotent evolution algebras are classified into three classes, and solvable ones are classified into five classes.